KUALITAS KEHIDUPAN KERJA, KEPEMIMPINAN DAN KEPRIBADIAN SERTA EMPLOYEE ENGAGEMENT PERANGKAT DESA DI KECAMATAN LABUHAN HAJI - Paelori, Daeng; Mulyono, Sugeng; Suswati, Endang; Sulaiman, Sulaiman (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2023)
This research aims to prove and analyze the influence of quality of work life, leadership and personality on employee engagement of village officials in Labuhan Haji sub-district, East Lombok Regency. The type of research used is explanatory research. The analysis technique is carried out using multiple linear regression. The results of this research are that simultaneously, the quality of work life, leadership and personality have a significant positive effect on employee engagement among village officials. Meanwhile, partially, quality of work life and leadership have no influence on employee engagement. Meanwhile, personality has a significant positive influence on employee engagement of village officials in Labuhan Haji sub-district, East Lombok district.